Majmūʿa-yi āthār-i Imāmiyah : Muntakhabātī az ʿUyūn-i akhbār-i Riḍā, Amāli-yi Shaykh-i Ṣaddūq, Ṣaḥīfat al-Riḍā - al-Bayhaqī, Abū Naʿīm al-Naʿīmi (Miras Maktoob, ISBN: 9789004365452., 2020)
At first glance, the collection of traditions, notes and drafts published here is just like so many other personal documents from the library of the average medieval Muslim scholar. But on closer inspection, this codex dated 580/1185 is quite interesting. The manuscript is in two different hands, one part being by a certain Abū Naʿīm al-Naʿīmi al-Bayhaqī, and the other part by the equally unknown Abu ʼl-Ḥasan al-Bayāḍī. As is evident from two study certificates ( ijāza ) contained in this manuscript, Abu ʼl-Ḥasan was a student of Abū Naʿīm. Abū Naʿīm was a native of Bayhaq and Abu ʼl-Ḥasan of Rayy. The manuscript contains mainly excerpts from Ibn Bābawayh's (d. 381/991) Amālī and ʿUyūn akhbār al-Riḍā and traditions which Abū Naʿīm himself had collected in Khurāsān. As such it contains the oldest known fragments from the Amālī , besides being a rare witness of the early Imami teaching tradition in Khurāsān, more specifically in Bayhaq and Nishapur.